Managerial Values as a Reflection of Culture and the Process of Industrialization - Whitely, William; England, George W. (Academy of Management Journal, 1977)
This study examines the relative roles of culture and industrialization as explanations for the similarities in the value systems of managers in five countries. Results indicate that both explanations play a role in the similarities and differences found in value systems. Focusing on either explanation ignores their mutual importance.